L’avant-corps de la tour philippienne du château de Chinon (Indre-et-Loire) : un exemple d’adaptation d’un standard architectural aux contraintes topographiques - Bruno Dufaÿ; Bastien Lefebvre; Samuel Riou (Revue Archéologique du Centre de la France)
The Coudray keep is a circular tower of the Philippe Auguste type. The tower type is not entirely classic, since, as opposed to others erected by the engineers of Philippe Auguste, it is served by a rectangular projection which gives access to the first floor. The excavation and detailed study of its elevations have enabled us to ensure that the unusual projection was really comptemporary with the tower. It was possible to reconstruct its missing sections with certainty. More than just an archaism contradicted by the care given to the building as a whole, the creators construed it as a short term answer to a topographic constraint.